Enthesitis in a European registry-based cohort of patients with psoriatic arthritis treated with tumour necrosis factor inhibitors - Mathew, A. J. (2024)
Funding Information: The EuroSpA Research Collaboration Network was financially supported by Novartis Pharma AG. Novartis did not influence data collection, statistical analyses, manuscript preparation or decision to submit the manuscript. The outline of was drawn by Mr Rajkumar, Department of Anatomy, Christian Medical College, Vellore, India. Publisher Copyright: © 2024 The Author(s). Published by Informa UK Limited, trading as Taylor & Francis Group.